2013
DOI: 10.1038/srep03440
|View full text |Cite
|
Sign up to set email alerts
|

Elevated cerebrospinal fluid and blood concentrations of oxytocin following its intranasal administration in humans

Abstract: There has been an unprecedented interest in the modulatory effects of intranasal oxytocin on human social cognition and behaviour, however as yet no study has actually demonstrated that this modality of administration increases concentrations of the peptide in the brain as well as blood in humans. Here using combined blood and cerebrospinal fluid (CSF) sampling in subjects receiving either 24 IU of oxytocin (n = 11) or placebo (n = 4) we have shown that oxytocin levels significantly increased in both plasma an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

23
368
2
5

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 421 publications
(398 citation statements)
references
References 27 publications
23
368
2
5
Order By: Relevance
“…Although we were unable to directly assess oxytocin in the CNS, this finding of elevated salivary oxytocin is consistent with studies in adult macaques that reported elevated CSF oxytocin levels 35-120 min after aerosolized oxytocin delivery (4,50). It is also consistent with studies in rodents reporting that intranasal oxytocin increases extracellular concentrations of oxytocin in behaviorally relevant brain regions, peaking 30-60 min after administration (51), and studies of elevated oxytocin in human CSF 75 min following intranasal administration (52). Although the relation between central and peripheral oxytocin levels has not been fully elucidated (e.g., ref.…”
Section: Discussionsupporting
confidence: 77%
“…Although we were unable to directly assess oxytocin in the CNS, this finding of elevated salivary oxytocin is consistent with studies in adult macaques that reported elevated CSF oxytocin levels 35-120 min after aerosolized oxytocin delivery (4,50). It is also consistent with studies in rodents reporting that intranasal oxytocin increases extracellular concentrations of oxytocin in behaviorally relevant brain regions, peaking 30-60 min after administration (51), and studies of elevated oxytocin in human CSF 75 min following intranasal administration (52). Although the relation between central and peripheral oxytocin levels has not been fully elucidated (e.g., ref.…”
Section: Discussionsupporting
confidence: 77%
“…First, two task-based fMRI scans were conducted: an emotional face-matching task (Koch et al, 2015) and a monetary (Nawijn et al, 2016a) and social (Nawijn et al, 2016b) incentive delay reward task. Hereafter, the resting-state scan was conducted, which began on average 72.51 min (±4.03) after intranasal spray administration, when neuropharmacological OT administration effects on cerebral blood flow (Paloyelis et al, 2014) and elevated OT levels in cerebrospinal fluid (Striepens et al, 2013) are still observed. During resting-state scanning, participants were instructed to relax and let their mind wander, with open eyes.…”
Section: Methodsmentioning
confidence: 99%
“…Subjects were randomly assigned to either intranasal administration of OXT (24 IU; Syntocinon-Spray, Novartis; three puffs per nostril, each with 4 IU OXT) or PLC (sodium chloride solution) 30 min before the start of the fMRI. The intranasal administration of OXT has been shown to increase OXT concentration in the CSF (Striepens et al, 2013). Details on the tasks, fMRI procedure, and analyses can be found in the Supplementary Information.…”
Section: Experimental Designmentioning
confidence: 99%